2011
DOI: 10.1080/17588928.2011.603828
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive drift without illusions of ownership for rotated hands in the “rubber hand illusion” paradigm

Abstract: The rubber hand illusion is one reliable way to experimentally manipulate the experience of body ownership. However, debate continues about the necessary and sufficient conditions eliciting the illusion. We measured proprioceptive drift and the subjective experience (via questionnaire) while manipulating two variables that have been suggested to affect the intensity of the illusion. First, the rubber hand was positioned either in a posturally congruent position, or rotated by 180°. Second, either the anatomica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 20 publications
10
101
0
Order By: Relevance
“…With regards to the proprioceptive drift results, the non-significant relationship between illusion strength and proprioceptive drift scores is in accordance with some previous studies [50], [52] but inconsistent with other findings [1], [24], [61], [62]. Moreover, the absence of a relationship between proprioceptive drift and schizotypal traits is in accordance with findings reported by Germine et al [29].…”
Section: Discussionsupporting
confidence: 50%
“…With regards to the proprioceptive drift results, the non-significant relationship between illusion strength and proprioceptive drift scores is in accordance with some previous studies [50], [52] but inconsistent with other findings [1], [24], [61], [62]. Moreover, the absence of a relationship between proprioceptive drift and schizotypal traits is in accordance with findings reported by Germine et al [29].…”
Section: Discussionsupporting
confidence: 50%
“…Secondly, the viewed body orientation provides a further important cue for one's own body: viewing a hand with fingers pointing away from one's trunk is anatomically more plausible for one's own hand than viewing a hand with the opposite orientation. The importance of this body ownership cue has been demonstrated also with the rubber hand illusion paradigm (Ehrsson et al 2004;Holle et al 2011;Ide 2013).…”
Section: Introductionmentioning
confidence: 90%
“…Therefore, it could be argued that the lack of a relationship between one aspect of the RHI (i.e., the explicit questionnaire) and hypnotic suggestibility implies no relationship between HS and the rubber hand illusion, as classically proposed. However, recent behavioural (Holle et al 2011;Kammers et al 2009;Wold et al 2014) and neuroimaging (Tsakiris et al 2007) findings have indicated that the RHI is a multi-facetted and complex illusion which can be broken down into separate constructs (e.g. Figure 1) and that separate cognitive multisensory mechanisms underlie different aspects of the illusion (Blanke 2012;Makin et al 2008;Rohde et al 2011;Tsakiris et al 2010).…”
Section: Discussionmentioning
confidence: 99%